Comparison of Neoadjuvant Chemotherapy Efficiency in Advanced Ovarian Cancer Patients Treated With Paclitaxel Plus Carboplatin and Intraperitoneal Bevacizumab vs. Paclitaxel With Carboplatin - Tao, Yin; Tang, Xue-Ting; Li, Xing; Wu, An-Shan; Zhou, Hou-Shen; Zhou, Cheng-fang (Frontiers in Medicine, 2022)
Objective This study evaluated the role of neoadjuvant chemotherapy (NACT) with bevacizumab intraperitoneal perfusion in advanced ovarian cancer (AOC). Methods In this study, 80 patients with advanced epithelial ovarian cancer (stage IIIc or IV) who received NACT at the Central Hospital of Zhuzhou between February 2019 and October 2020 were enrolled. Patients were randomized to receive paclitaxel plus carboplatin (TC) or TC plus intraperitoneal perfusion of bevacizumab (TCB). The effect of chemotherapy was assessed following two cycles of chemotherapy. Cancer antigen 125 (CA125), tumor size, ascites volume, bleeding volume, duration of operation, surgical satisfaction rate, complication rate, and residual tumor were assessed to monitor response to chemotherapy. Results Treatment with TCB regimen significantly reduced serum levels of CA125 and ascites volume (p < 0.001). Meanwhile, the TCB group had significantly lower intraoperative blood loss and shorter operation time (p < 0.001). Most importantly, patients treated with TCB regimen had a higher surgical satisfaction rate (p < 0.01). Moreover, the incidence of postoperative wound infection, hypoproteinemia, abdominal distension, and fever was lower in the TCB group compared with the TC group. Assessment of adverse reactions during chemotherapy showed no severe complications between the two groups. Conclusions The results demonstrated that the TCB regimen is superior to the TC regimen alone in the treatment of AOC. These findings could help improve the surgical satisfaction rate, provide more effective treatment strategies to prolong progression-free survival and reduce postoperative complications, and promote surgical recovery in AOC.